(untitled) (Research, Society and Development, 2024)
The correct selection of the transmucosal profile is essential for successful planning and treatment of implant-supported rehabilitations. For this, the dental surgeon must verify the specificities of each clinical case and use imaging tests such as periapical radiography, use of a millimeter periodontal probe, and transmucosal gauges, to aid in the evaluation, measurement and adequate choice of the component. This relationship aims at maintaining the bone tissue, preventing pain, inadequate pressure on the tissues, bone saucerization, etc. Thus, this work aims to present a case report of implant installation in the region of teeth 15 and 26, associated with the appropriate selection of transmucosal components for surgery.